G477(P) Benign premature adrenarche; a review of current management. (27th April 2016) - Lwin, T; Coren, M
Abstract : Introduction: Benign Premature Adrenarche (BPA) is defined as the presence of secondary sexual hair growth in girls under 8 and boys under 9 years of age in the absence of other pathology. No guidelines currently exist for the management of BPA. At St. Mary's Hospital, current practice involves clinical examination and biochemical tests to exclude other pathologies to diagnose BPA. Our aim was to review current practice in order to identify methods for which we can improve diagnosis and management, potentially forming the basis for new guidelines. Methods: Data collection involved retrospective analysis of 35 patient letters (30 female, 5 male) to GPs from the paediatric outpatient population at St. Mary's. Letters were dated from 2009 onwards. Data included clinical and biochemical examination findings, the total number of consultations and symptom duration before consultation. Results: On clinical examination, no patients reported breast development above Tanner's Stage 2. 64.3% (n = 28) of patients had pubic hair development in Tanner stages 2–3, whilst 42.9% (n = 28) had Tanner stage 2 for axillary hair development. 81.5% (n = 27) of patients reported that their symptoms lasted for over 4 months. 91.4% (n = 35) of patients received blood tests for androgens and 17-hydroxyprogesterone; all coming back with normal findings. 51.5% (n = 33) of patients were reviewed in paediatric clinic twice before being discharged back to their GP. Conclusions: The results of the clinical and biochemical findings indicated that all patients in our study most likely had a diagnosis of BPA. The majority of these patients waited >4 months before seeing healthcare advice. Some required multiple clinic appointments for reassurance. Our study reveals that biochemical testing yields little information, as all of our patients had normal blood results. Therefore, we recommend efforts should be made to decrease consultant-led outpatient care and minimise investigation for management of patients with BPA.